Carbene footprinting accurately maps binding sites in protein–ligand and protein–protein interactions - Lucio Manzi (Nature Portfolio, 2016)
Mapping protein-ligand interactions is fundamental to advance the understanding of cellular processes and to develop drug discovery strategies. Here, the authors present a photo-activated probe that allows highly efficient labelling and identification of protein binding sites using mass spectrometry.